I diritti degli indigeni saami all'uso comune delle terre nel Finnmark (Norvegia del Nord) - MAZZA, Mauro (Giappichelli, 2013)
The article examines the legal status of the Saami in the County of Finnmark, in Northern Norway. The provisions of both domestic law and international law are analyzed, as well as the main Norwegian judicial decisions. Some problematic aspects of the Finnmark Commission and the Land Tribunal for Finnmark are highlighted, also in view of the possible reform of the legislation concerning the protection of the indigenous population.